Perceived Impact of Primary Education on the Attainment of Nigeria Vision 20:2020 - Adesina, Abiodun Ezekiel (Richtmann Publishing, 2011)
This study sought the perceived impact of primary education on the attainment of Nigeria Vision 20:2020. Surveydesign was adopted for the study. Six hundred primary school teachers were randomly sampled from Oyo Local GovernmentAreas of Oyo State. A self-designed 20 items questionnaire validated and trial-tested with reliability of 0.83 was used to collectthe data. Three hypotheses were tested at 0.05 level of significance using t-test statistical tool. The findings revealed that theprimary education standard have impact on the nation attainment of NV 20:2020 (cal-t = 10.73; Crit-t= 1.96, df = 598) and thatthe standard of primary education is hampered by the low level of funding and facilities availability at school (Cal-t = 11.06, Crit-t= 1.96, df = 598). Also it was found that the level of teachers qualification at the primary school significantly influence thestandard of primary education in the country (Cal-t = 4.66, Crit-t = 1.96, df = 598). It was therefore recommended that alongproper funding and facilities provision for primary level of education, liberalization should be encouraged for better qualifiedteachers to handle foundational classes in order for the nation to achieve her Vision 20:2020.